Effect of textile surface treatment on the flexural properties of textile-reinforced cementitious composites. (July 2016) - Pakravan, Hamid R; Jamshidi, Masoud; Rezaei, Hojatolah
In this study, the influence of a new surface treatment of the textiles to reinforce concrete materials has been investigated. The short polyvinyl-alcohol fibers were attached to the textile surface to achieve a fluffy textile. The flexural and peel tests were employed to study the effectiveness of the surface treatment on the carbon textile. As a result, the applied treatment considerably improved the bond properties between the textile and cement matrix up to 43%, and enhanced load-bearing capacity of textile-reinforced cementitious composites by up to 56%.